TRIPs as an adjustment mechanism in North-South trade - Gerhard Fisch; Bernhard Speyer (Intereconomics, 1995)
Developing countries tend to take a negative view of the protection of intellectual property rights as reflected in the TRIPs agreement, as this seems to conflict with their own developmental needs. As the following article points out, there are, however, a number of reasons why developing countries, too, may benefit from stronger protection of intellectual property rights.
Keywords: 330; Intellectual Property Rights